2021
DOI: 10.3390/w13131721
|View full text |Cite
|
Sign up to set email alerts
|

Urban Flood Management through Urban Land Use Optimization Using LID Techniques, City of Addis Ababa, Ethiopia

Abstract: In recent years, many urban areas in Ethiopia have experienced frequent flood events as a result of climate change and urban sprawl. Unplanned and unsustainable poor urban storm water management strategies will aggravate the impact and frequency of flood occurrence. In this study, impacts of urbanization and climate change on generated flood magnitude are analyzed using the urban hydrological model of Storm Water Management Model (SWMM) and Low Impact Development (LID) sustainable land use optimization techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Climate change in Addis Ababa is manifested by an increase in rainfall and subsequent flooding and severe temperature, with more heat-wave occurrences [57,[59][60][61]64,98]. The major direct impacts of climate change in the city are flooding, drought and urban heat island (UHI) [99] (Figure 3).…”
Section: Climate-change Impacts and Responses In Addis Ababa Citymentioning
confidence: 99%
See 2 more Smart Citations
“…Climate change in Addis Ababa is manifested by an increase in rainfall and subsequent flooding and severe temperature, with more heat-wave occurrences [57,[59][60][61]64,98]. The major direct impacts of climate change in the city are flooding, drought and urban heat island (UHI) [99] (Figure 3).…”
Section: Climate-change Impacts and Responses In Addis Ababa Citymentioning
confidence: 99%
“…Addis Ababa City is highly affected by climate change, such as flooding, drought, heat waves and land slides [57][58][59][60][61]. In the city, climate change and its impacts are aggravated by an unprecedented rate of urbanization and rapid population growth, built-up-area expansion, less green-area coverage and land use change [57,[62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the acceleration of global urbanisation, the impervious area of urban areas has increased sharply, resulting in a significant reduction in rainwater infiltration. This shortens the concentration time of rainfall and increases the peak of runoff, causing frequent urban waterlogging [1][2][3]. Moreover, the groundwater in urban areas cannot be effectively recharged, causing the groundwater level to decline year by year [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of flood peak discharge by each return period of storms was estimated to be about 7 to 15% at a wider catchment scale. Jemberie and Melesse [22] analyzed the impacts of urbanization and climate change on generated flood magnitude, using the urban hydrological model of SWMM and LID sustainable land use optimization technique, and pointed out that combined LID techniques have a significant impact on urban flood reduction of up to 75%. Samouei and Zger [23] investigated the hydrologic response of the catchment after replacing proportions of impervious surfaces with combinations of LID practices, and the results showed that implementing 5-20% of LIDs has a noticeable impact on runoff peak flow and volume reduction, especially in storm events with shorter return periods.…”
Section: Introductionmentioning
confidence: 99%